CHARACTERISTIC FEATURES OF THE COMORBID COURSE OF ALCOHOLISM AND SCHIZOAFFECTIVE DISORDERS - Vitaly Sergeevich, Sedenkov; Shoxrux Xabibullayevich, Sultanov; Bobir Temirpulotovich, Turayev (PT. Antis International Publisher, 2025)
Objective: This study aims to investigate the characteristic features of the comorbid course of alcoholism and schizoaffective disorders, focusing on the interplay between neurobiological mechanisms and clinical outcomes in patients with dual diagnoses. Method: A comprehensive review of clinical data and neurobiological studies was conducted, analyzing treatment approaches and the convergence of pathophysiological processes in patients with co-occurring alcohol dependence and schizoaffective disorders. Particular attention was given to the role of the dynorphin kappa-opioid system as a modulator of mesocorticolimbic dopaminergic system activity, which is implicated in both mental disorders and substance addiction. Results: The findings indicate that comorbid patients exhibit more severe clinical symptoms, poorer prognoses, and reduced treatment efficacy compared to individuals with singular diagnoses. The dysregulation of the dynorphin kappa-opioid system contributes to the exacerbation of both psychotic and addictive symptoms, complicating therapeutic interventions. Novelty: This study highlights the critical role of the dynorphin kappa-opioid system as a universal modulator in the pathogenesis of schizoaffective disorders and alcoholism, emphasizing the need for integrated treatment strategies that target both neurobiological and clinical dimensions of comorbidity.